Precipitation of Calcium, Magnesium, Strontium and Barium in Tissues of Four Acacia Species (Leguminosae: Mimosoideae) - He, Honghua (Public Library of Science, 2012)
Precipitation of calcium in plants is common. There are abundant studies on the uptake and content of magnesium, strontium and barium, which have similar chemical properties to calcium, in comparison with those of calcium in plants, but studies on co-precipitation of these elements with calcium in plants are rare. In this study, we compared morphologies, distributional patterns, and elemental compositions of crystals in tissues of four Acacia species grown in the field as well as in the glasshouse. A comparison was also made of field-grown plants and glasshouse-grown plants, and of phyllodes of different ages for each species. Crystals of various morphologies and distributional patterns were observed in the four Acacia species studied. Magnesium, strontium and barium were precipitated together with calcium, mainly in phyllodes of the four Acacia species, and sometimes in branchlets and primary roots. These elements were most likely precipitated in forms of oxalate and sulfate in various tissues, including epidermis, mesophyll, parenchyma, sclerenchyma (fibre cells), pith, pith ray and cortex. In most cases, precipitation of calcium, magnesium, strontium and barium was biologically induced, and elements precipitated differed between soil types, plant species, and tissues within an individual plant; the precipitation was also related to tissue age. Formation of crystals containing these elements might play a role in regulating and detoxifying these elements in plants, and protecting the plants against herbivory.